(untitled) (World Bulletin of Education and Learning, 2025)
The Uyghur Twelve Maqams have a long history, breadth, and depth. The muqams are accompanied by historical periods experienced by the Uyghur people. Muqams are folk music created in many places and in several periods by many musicians, singers, and musicians of the Uyghur people. This time, the twelve muqams, reorganized, integrated, and improved in succession, consist of 360 songs and 4,492 lines. In addition, it includes poems by Uyghur classical poets, Uyghur folk fragments, and folk songs.